PLAGIARISME DETECTION SYSTEM ON THIEF FACULTY OF COMPUTER SCIENCE UNIVERSITY U'BUDIYAH INDONESIA BASED TEXT MINING - TB, Desita Ria Yusian; Fathiah, Fathiah (Ubudiyah Indonesia University, 2016)
Plagiarism is the act of intentionally or unintentionally in obtaining ortrying to obtain credit or value to scientific work., citing part or all of thework / or scientific work of others who are recognized as scientific works,co without stating the source appropriately and adequately. Problem ofplagiarism has become a phenomenom that is being discussed inacademic forums. Based on a variety of information about the practice ofplagiarism is increasingly disturbing, this study conducted at the UbudiyahUniversity Indonesia (UUI). This system will implemented the detectionsystem plagiarism that will be creating using a document apllied method ofvector space model to analyze similarities in document displayed on theweb browser. Input on this system is a document in the form of text formatwhith the extention test performed on real data that is usig data documentswith vector space model algorithm value is above 85% to 100% for highlevel document. As for a document with a low degree of similarity valuesbelow 50%.Keyword : Plagiarism, Vector Space Model, Similarity